Overtraining syndrome in aquatic sports - Shagdan, B.
It is no secret among athletes that in order to improve performance they should work hard. Some athletes fail to recover from training, become progressively fatigued, and suffer from prolonged underperformance. They may also suffer from frequent minor infections particularly respiratory infections. This condition is called the over-training syndrome. There are some other names for similar conditions like burnout, staleness or sports fatigue syndrome. There is an idea that in the absence of any medical cause, overtraining is more accurately called the Unexplained Underperformance Syndrome (UPS). This definition is the result of several years of research and studies by Dr. Richard Budgett and his colleagues in the British Olympic Medical Centre (BOMC). "The condition is normally secondary to the stress of training and immune system impairment but the exact cause is not known, and many factors other than hard training and competition may lead to failure to recover from training or competition. The diagnosis is made if an athlete fails to recover despite two weeks of relative rest in the absence of a medical cause. UPS is most common in endurance athletes such as swimmers, cyclists, middle and long distance runners, kayakers and rowers. It is extremely rare in pure sprint and power athletes. Changes in psychological, hormonal and immune parameters have been shown in these under-performing athletes some of which may be useful as markers when used on an individual basis. Monitoring mood state, performance and heart rate may be helpful in some athletes. However the importance of any of these changes, many of which are seen in athletes without UPS when training very hard, is not fully understood. Athletes normally recover in 6 to 12 weeks with regeneration strategies and a programme of gentle exercise far below their normal intensity. Once 20 minutes is easily tolerated then short sprints can be introduced" (Budgett et al).